2017
DOI: 10.20533/ijcdse.2042.6364.2017.0413
|View full text |Cite
|
Sign up to set email alerts
|

Eportfolio Implementation in a Multiple Campus University Environment 6 – Academic Teacher Continuous Improvement

Abstract: At the Australian Catholic University (ACU) an ePortfolio may be used as a product, to display parts of one's Personal Learning Environment (PLE), or as a process, referred to as a Personal Learning Network (PLN). This is challenging to institutions and their Executive, as academics can use it both as an assessment 'of' learning and as a vehicle 'for' learning. It promotes metacognitive awareness of learning (awareness of one's own thinking and problem solving) providing opportunities for selfdirected learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In contrast, the quantitative data showed that the e-portfolio was rated as the least effective among program components. This finding confirms similar reported challenges on e-portfolios (Fisher & Hill, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the quantitative data showed that the e-portfolio was rated as the least effective among program components. This finding confirms similar reported challenges on e-portfolios (Fisher & Hill, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…One key strategy to encourage ownership is to highlight how they could use this document for multiple purposes such as achieving internship and/or pursuing employment positions. It is preferable to ensure that 13 academic teaching staff have their own 'living' E-Portfolios (Fisher & Hill, 2017) as they serve as an example to students regarding how E-portfolios are successfully used by their mentors as part of their everyday practice.…”
Section: Tip 4: Developing Assessmentsmentioning
confidence: 99%
“…It can present these documents and evidence to one or more audiences. In addition, it can provide bene ts such as increasing motivation in students, sharing contents with evaluators and other students, hyperlinking the data, easily updating contents, easily accessing portfolios for both students and schools, reducing paper consumption, making students reconsider and nally students can recognize their strengths and weaknesses in their academic years (10,11). However, there are aws such as the requirement for an internet connection and computer skills as well as ethical challenges, which in some cases cause students and teacher to be reluctant to use this assessment system (12) Therefore, it is recommended that in addition to emphasizing the several bene ts of this system of assessment on students' learning, this system be used mandatorily in medical science universities.…”
mentioning
confidence: 99%